Pulse Width Modulation (PWM) and Pulse Amplitude Modulation (PAM) Technique for Medium-Speed BLDCM in Electric Vehicle Application - Rizani Rusli, Muhammad; Rahmatullah, Haris; Badriatul Fauziah, Melinda; Jaya, Arman; Machmud Rifadil, Mochammad; Purwanto, Era (2018 International Seminar on Application for Technology of Information and Communication, 2018)
High torque and high efficiency are two factors used as a consideration of why many electric vehicles (EV) use brushless DC motor (BLDCM) as a propulsion system. Likewise, Amtenar car -a PENS's electric car- use this kind of motor as its propulsion. BLDCM can be driven by two techniques. They are Pulse Amplitude Modulation (PAM) and Pulse Width Modulation (PWM) technique. Both techniques are applied to the Amtenar car using the STM32F4 microcontroller to observe the dynamic speed response and efficiency which is operated under no-load conditions and on a load of Amtenar car. PWM scheme uses H-PWM-L-ON while PAM technique employes DC-DC buck converter. When PAM technique is applied to a no-load condition, PAM technique produces higher speed and efficiency and also produces a better dynamic speed performance as compared to PWM technique. While, when both techniques are applied to Amtenar car in the same line-to-line RMS voltage reference, PAM technique generates higher speed and has better dynamic speed performance than PWM technique. According to the comparative study of two techniques that have been observed in this paper, an efficient and high-performance technique for the BLDCM drive as an EV propulsion can be determined.